About Some Physical Properties of Water in Nanosistems and the Possible Mechanism of Superconductivity Induction by Water in Compounds and - Martseniuk, Oleksandr; Martseniuk, Liudmyla; Kurik, Mikhail (My University, 2013)
Work is devoted to the analysis of properties of water, diffused in the layered compounds and . We offer for the first time the mechanism of effect, recently opened by the Japanese researchers, of inducing of superconductivity by water in these compounds. For this purpose a positions of the theory of water molecules condensation in a liquid states, developed by J.Preparata from a statements of quantum electrodynamics, have been used. Water, diffused in compounds, forms nanosistems, - the individual layers, parallel to ferriferous layers of compounds, and at some properties is similar to EZ-water, which are well described by this theory. Therefore it is necessary to expect, that at low temperatures such nanowater will differ from usual ice.
Keywords: nanowater; coherent domains; SPE-effect; coherent water; near- surface water; EZ-water; water phases; нановода; когерентные домены; СПЕ- эффект; когерентная вода; приповерхностная вода; EZ-вода; фазы воды; свойства воды; когерентні домени; СПЕ- ефект; когерентна вода; приповерхнева вода; фази води; властивості води; кафедра процесів і апаратів харчових виробництв